Scientific production on Gerodontology as a dental specialty – Bibliometric literature review - de Castilhos, Eduardo Dickie; Rodrigues Junior, Sinval Adalberto (Revista FisiSenectus, 2023)
Introduction: Gerodontology or ‘geriatric dentistry’ exists as a field since the 1970s. However, its presence in the undergraduate dental curriculum is limited and distorted even today. Aim: Therefore, this study aimed to characterize the scientific production on gerodontology. Methodology: Studies focusing on gerodontology were searched in PubMed NCBI in November 2022 and constituted a database that was analyzed in Bibliometrix 4.0 for R. Descriptive and network analysis were applied to data. The conceptual structure analysis involved keywords co-occurrence network and thematic map. Results: The scientific production in the field of Gerodontology has a 7.2% annual growth rate. Japan is the most productive country in the field, followed by Switzerland. Most of the ten more productive journals are related to conventional dental specialties, such as clinical dentistry, prosthetics and dental implant. The analysis of the conceptual structure presented the current tendency of observational studies addressing the oral health and the quality of life of old people and related factors. Testing of materials meant for oral rehabilitation was found with lower relevance and densely studied during the assessed time spam. Conclusion: The profile of publication and the themes addressed in gerodontology focus on the association of oral conditions and risk factors. Testing of materials and teaching of gerodontology are also explored. Still, important issues such as prejudice related to ageing, working market of gerodontology and the formation of qualified personnel in the field still require further study.